ANTIBACTERIAL POTENTIAL OF Nicotiana tabacum LEAVES EXTRACTS AND THEIR ANTIOXIDANT ACTIVITIES - Putri, Devi Anggraini; Fahmi, Norma Farizah; Mawli, Rizka Efi; Fatmawati, Sri (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
Nicotiana tabacum, recognized as tobacco, has been reported its secondary metabolites and biological activities in the past decade. Madura is one of the islands in Indonesia that produces N. tabacum rapidly. In Madura, N. tabacum is called as bhekoh. Previously, antioxidant activity of N. tabacum leaves extracts has been reported. However, the extracts showed very low antioxidant activity due to low of the stock concentration. Accordingly, this research was aimed at the antibacterial and antioxidant evaluation of N. tabacum leaves from Madura with improvement of the concentration. Furthermore, N. tabacum leaves were extracted by using different solvents including n-hexane, dichloromethane, ethyl acetate, acetone, and methanol. The extracts have been evaluated their antibacterial activities by using colorimetric resazurin microtiter assay (REMA) method. The extracts have been assayed their antibacterial activities against both gram-positive and negative bacteria. While, the antioxidant evaluation has been determined by using 2,2-diphenyl-1-picryl-hydrazyl (DPPH) method. The result showed that the extracts have fine antibacterial and antioxidant activities. The methanol extract presented antioxidant activity with IC50 of 12.12 ppm compared to gallic acid as a standard. Furthermore, the acetone extract showed the highest antibacterial activity against Bacillus subtilis, Propionibacterium acnes, and Salmonella typhi with MIC of 0.31, 0.63, and 0.63 mg/mL, respectively, compared to ampicillin as a standard. In conclusion, the acetone and methanol extracts have the highest antibacterial and antioxidant activities. Therefore, our result suggested acetone and methanol extracts of N. tabacum leaves as antibacterial and antioxidant agents.